MASA DEPAN STUDI ISLAM DI PENDIDIKAN TINGGI KEAGAMAAN ISLAM (Sebuah Tinjauan Filosofis-Yuridis) - Rohman, Miftahur; Syahril, Sulthan; Fauziyati, Dini (IAIN Ponorogo, 2018)
Higher Education of Islamic Religion (PTKI) become an integral part of the development of Islamic civilization in Indonesia. According to the reason, it is needed a renewal of education system that can produce graduates who are globally competitive, have social skills, and have multicultural character. This research attempts to formulate an integration model of science and religion in Islamic studies at PTKI to create ideal graduates who are aspired. By tracking literature and using a philosophical approach to the theory of spider webs by Amin Abdullah, it can be concluded that Islamic studies at PTKI that focused on the study of religious sciences (ulÅ«m al-dÄ«n), it must be held a dialogue with modern scientific disciplines and must always in critical-analytic studies. Practically this integration is realized in the form of reinterpretation of religious texts in order to answer complex social problems. Thus, besides having academic provision, graduates of PTKI are expected to have social intelligence, diversity character, and not rigid to differences.Ø£ØµØ¨ØØª Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø±ØÙØ© Ø§ÙØ¬Ø§Ù Ø¹ÙØ© Ø¬Ø²Ø¡Ø§ ÙØ§ ÙØªØ¬Ø²ÙØ¡ ÙÙ Ø¨ÙØ§Ø¡ Ø§ÙØ«ÙØ§ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§. Ø¨ÙØ°Ø§ ØªØØªØ§Ø¬ Ø§ÙØØ§ÙØ© Ø¥ÙÙ Ø§ÙØªØºÙÙØ± ÙØ§ÙØªØ¬Ø¯ÙØ¯ ÙÙ ÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙ Ø·Ø¨ÙØ© ÙØªØ®Ø±ÙØ¬Â Ø§ÙØ®Ø±ÙÙØ¬ÙÙ Ø°ÙÙ Ø±ÙØ Ø§ÙÙ ÙØ§ÙØ³Ø© Ø§ÙØ¹Ø§ÙÙ ÙØ©Ø ÙØ§ÙÙØ¯Ø±Ø§Øª Ø§ÙØ§Ø¬ØªÙ Ø§Ø¹ÙØ©Ø ÙØ§ÙØ®ÙÙ Ø§ÙÙ ØªØ¹Ø¯Ø¯ Ø§ÙØ«ÙØ§ÙØ§Øª. ØØ§ÙÙØª ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙØ¶Ø¹ ÙÙ ÙØ°Ø¬ Ø§ÙØªÙ Ø²ÙØ¬ Ø¨ÙÙ Ø§ÙØ¹ÙÙÙ ÙØ§ÙØ¯ÙÙ ÙÙ Ø§ÙØ¯Ø±Ø§Ø³Ø§Øª Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©Â Â Â ÙÙ Ø§ÙØ¬Ø§Ù Ø¹Ø§Øª Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø¨ÙØ¯Ù ØªØ®Ø±ÙØ¬ Ø§ÙØ®Ø±ÙØ¬ÙÙ Ø§ÙÙ Ø«Ø§ÙÙÙÙ.Â ÙØ¨Ø¯Ø±Ø§Ø³Ø© Ø£ÙÙØ§Ø¹ Ù Ù Ø§ÙÙ ØµØ§Ø¯Ø± ÙØ§ÙÙ Ø±Ø§Ø¬Ø¹ ÙØ¨Ø§ÙÙ Ø¯Ø®Ù Ø§ÙÙÙØ³ÙÙ ÙÙØ¸Ø±ÙØ© Ø´Ø¨ÙØ© Ø§ÙØ¹ÙÙØ¨ÙØª ÙØ£Ù ÙÙ Ø¹Ø¨Ø¯ Ø§ÙÙÙØ ÙÙ ÙÙ Ø§ÙØ§Ø³ØªÙØªØ§Ø¬ Ø£Ù Ø§ÙØ¯Ø±Ø§Ø³Ø§Øª Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙØ¬Ø§Ù Ø¹Ø§Øª Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙÙ Ø±ØªÙØ²Ø© Ø¹ÙÙ Ø¯Ø±Ø§Ø³Ø© Ø§ÙØ¹ÙÙÙ Ø§ÙØ¯ÙÙÙØ© ÙØ§Ø¨Ø¯ Ù Ù Ø±Ø¨Ø·ÙØ§ Ø¨Ø§ÙØ¹ÙÙÙ Ø§ÙØ¹ØµØ±ÙØ© ÙÙØ§Ø¨Ø¯ Ø£Ù ØªÙÙÙ Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ Ø¸Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙÙØ¯ÙØ© ÙØ§ÙØªØÙÙÙÙØ©. ÙÙÙ Ø§ÙÙØ§ÙØ¹Ø ÙØ§Ù ÙØ°Ø§ Ø§ÙØªÙ Ø²ÙØ¬ ÙØªÙ Ø«ÙÙ ÙÙ Ø§Ø³ØªÙØ¨Ø§Ø· Ø§ÙÙ Ø¹ÙÙ Ø§ÙØ¬Ø¯ÙØ¯ Ù Ù Ø§ÙÙØµÙØµ Ø§ÙØ¯ÙÙÙØ© ÙØÙ Ø§ÙÙ Ø´Ø§ÙÙ Ø§ÙØ§Ø¬ØªÙ Ø§Ø¹ÙØ© Ø§ÙØªÙ Ø£ØµØ¨ØØª Ù ØªØ¹ÙØ¯Ø©. Ø¨ÙØ°Ø§ ÙØ¹ÙÙ Ø®Ø±ÙØ¬ Ø§ÙØ¬Ø§Ù Ø¹Ø§Øª Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø£Ù ÙØ³ØªÙÙÙØ§ Ø¹ÙÙ Ø§ÙØ¨Ø¶Ø§Ø¦Ø¹ Ø§ÙØ£ÙØ§Ø¯ÙÙÙØ© ÙØ¨Ø¬Ø§ÙØ¨ Ø°ÙÙ Ø£Ù ÙÙÙÙ ÙÙÙ Ø§ÙØ°ÙØ§Ø¡ Ø§ÙØ¥Ø¬ØªÙ Ø§Ø¹Ù ÙÙØ¨ÙÙ Ø§ÙØªÙÙÙØ¹Ø§ØªÂ ÙØ³Ù Ø§ØØ© ÙÙ ÙØ§Ø¬ÙØ© Ø§ÙØ§Ø®ØªÙØ§ÙØ§Øª